CDK4/CDK6 inhibitors synergize with Midostaurin, Avapritinib, and Nintedanib in inducing growth inhibition in KIT D816V+ neoplastic mast cells - Schneeweiss-Gleixner, Mathias; Filik, Yüksel; Stefanzl, Gabriele; Berger, Daniela; Sadovnik, Irina; Bauer, Karin; Smiljkovic, Dubravka; Eisenwort, Gregor; Witzeneder, Nadine; Greiner, Georg; Hoermann, Gregor; Schiefer, Ana-Iris; et al. (Cancers, 2022)
In most patients with advanced systemic mastocytosis (AdvSM), neoplastic mast cells (MC) express KIT D816V. However, despite their disease-modifying potential, KIT D816V-targeting drugs, including midostaurin and avapritinib, may not produce long-term remissions in all patients. Cyclin-dependent kinase (CDK) 4 and CDK6 are promising targets in oncology. We found that shRNA-mediated knockdown of CDK4 and CDK6 results in growth arrest in the KIT D816V+ MC line HMC-1.2. The CDK4/CDK6 inhibitors palbociclib, ribociclib, and abemaciclib suppressed the proliferation in primary neoplastic MC as well as in all HMC-1 and ROSA cell subclones that were examined. Abemaciclib was also found to block growth in the drug-resistant MC line MCPV-1, whereas no effects were seen with palbociclib and ribociclib. Anti-proliferative drug effects on MC were accompanied by cell cycle arrest. Furthermore, CDK4/CDK6 inhibitors were found to synergize with the KIT-targeting drugs midostaurin, avapritinib, and nintedanib in inducing growth inhibition and apoptosis in neoplastic MCs. Finally, we found that CDK4/CDK6 inhibitors induce apoptosis in CD34+/CD38- stem cells in AdvSM. Together, CDK4/CDK6 inhibition is a potent approach to suppress the growth of neoplastic cells in AdvSM. Whether CDK4/CDK6 inhibitors can improve clinical outcomes in patients with AdvSM remains to be determined in clinical trials.
Im Titel ist "+" hochgestellt
Gesehen am 23.08.2022